Dynamic contrast-enhanced MR and PET/CT findings of uterine sarcomatoid carcinoma: a case report - Tingting Cui; Yanfang Jin; Bin Li; Jiyuan Li; Yunlong Yue (BMC, 2020)
Abstract Background Sarcomatoid carcinoma (SC) is a malignant tumour composed of spindle cells. The incidence of SC is low, especially in the uterus. The imaging features of uterine sarcomatoid carcinoma (USC) are rarely reported. We report a case of USC and discuss the dynamic contrast-enhanced MR (DCE-MR) and PET/CT findings. Case presentation A 69-year-old woman presented to the Department of Gynaecology with vaginal bleeding. Ultrasound examination discovered a heterogeneous mass in the cervix. Then, MRI examination of the pelvis was performed. On T2-weighted images, the uterus was replaced by an ill defined and diffuse lesion with inhomogeneous intensity. On T1-weighted images, the lesion appeared with signal hypointensity and was heterogeneously enhanced with contrast material. Additionally, enlarged lymph nodes were found in the pelvic cavity. PET/CT demonstrated high uptake in the region of the uterus and pelvic lymph nodes, which was consistent with MRI findings. The radiologists diagnosed the patient with malignant uterine lesions. The patient underwent hysterectomy and bilateral adnexectomy with pelvic lymph node dissection. Then, systemic radiotherapy and chemotherapy were performed. USC with lymph node metastasis was diagnosed with the help of immuno-histochemical analysis. There was no treatment related complication and no evidence of tumour recurrence at the postoperative 6-month follow-up. Conclusion MRI and PET/CT features are sufficient to indicate the malignant nature of a USC, but they are not pathognomonic.